2002
DOI: 10.1097/00004647-200207000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aspects of Stroke: Human and Experimental Studies

Abstract: As one of the leading causes of death within both the developed and developing world, stroke is a worldwide problem. Risk factors can be identified and controlled at the level of lifestyle changes; however, genetic components of stroke have yet to be identified. The identification of such genetic components is critical in the understanding, diagnosis, and treatment of stroke in the future. This review focuses on the genetic determinants of stroke in both human and experimental systems. Mendelian disorders, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 87 publications
(83 reference statements)
0
29
0
Order By: Relevance
“…The identification of genetic components of stroke and neurodegenerative disease linked to TBI is critical to the understanding, diagnosis, and treatment of these injuries (Carr et al, 2002;Longhi et al, 2001). While risk and environmental factors can be identified and controlled, genetic determinants of disease, in addition to conferring an enhanced vulnerability to other neurodegenerative disorders, pose a challenging problem for investigative studies.…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of genetic components of stroke and neurodegenerative disease linked to TBI is critical to the understanding, diagnosis, and treatment of these injuries (Carr et al, 2002;Longhi et al, 2001). While risk and environmental factors can be identified and controlled, genetic determinants of disease, in addition to conferring an enhanced vulnerability to other neurodegenerative disorders, pose a challenging problem for investigative studies.…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
“…Also, genetically engineered mice that typically over-express or have a specific gene deleted (knock-out) have been developed to study the cause-and-effect relationships in specific injury pathways (Chan et al, 1995). These include the use of mice targeting antioxidant processes, adhesion molecules, interleukins, matrix metalloproteases (MMPs), apoptotic genes, and nitric oxide (Carr et al, 2002).…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
“…Our findings underline the fact that stroke is a polygenic disorder (20 ). The effects of gene-gene as well as gene-environment interactions on the predisposition to cerebrovascular disease are still under investigation.…”
Section: Discussionmentioning
confidence: 52%
“…Stroke is diffi cult to study from a molecular point of view, because of its gene-environment interactions, genetic and nongenetic heterogeneity, polygenic inheritance with variable penetrance and not least, late age of onset [6]. Candidate genes, stroke susceptibility alleles and their association with stroke pathogeny have been intensely studied in the last few years [7,8,9]. Immunity and infl ammation are key elements of the pathobiology of ischemic stroke [10], several studies have shown that the serum of patients with stroke highlights increased levels of proinfl ammatory cytokines, and therefore support the hypothesis promoting their involvement in the etiopathogenesis of the disease [11,12].…”
Section: Introductionmentioning
confidence: 99%